Report on the Conference of History of Mathematics & Teaching of Mathematics with Special Subject Ethno-mathematics: Research in History of Mathematics & Teaching of Mathematics : University of Miskolc, 18–21 May, 2006, Miskolc, Hungary (Teaching Mathematics and Computer Science, 2006)
The 4th Conference on History of Mathematics & Teaching of Mathematics with Special Subject Ethno-mathematics was organized at the University of Miskolc (Hungary). The aim of the conference was to present aspects of the History of Mathematics and Ethno-mathematics, including its impact on the Teaching of Mathematics.Its motto was: Mathematics – a common language for Europe for thousand years.There were 21 presentations, a poster lecture (J. Kolumbán, University of Cluj, Romania) and an exhibition made by students of Eötvös University, Budapest (R. Tanács, K. Varga).After a short historical introduction we present 19 abstracts and the poster lecture.